THE FOLK POEM OF THE KARAKALPAK PEOPLE “SARYSHA AYM TOLGAVY” AS RENDERED BY UZAKBERGENLY BERDIMURAT BEKBERGEN UULU (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This academic work is dedicated to the study of the folk poem “Sarysha Aym,” recorded in April 2024 in Karakalpakstan during ethnographic field research. The poem was narrated by an 88-year-old aksakal, Uzakbergenly Berdimurat Bekbergen Uulu, a representative of the Baltaly-Mailybalta clan of the Kipchak tribe of the Karakalpak people, residing at Kok-Saray Street, house№39, in the Erezhep Biy mahalla of Shatly village, Bozau District, Nukus City. The aksakal’s phenomenal ability to recite the poem from memory astonished the researchers. The informant demonstrated not only exceptional skill in conveying the folk epic but also unique personal qualities that left an unforgettable impression. An audio recording made during the session was transcribed and subjected to historical-ethnographic and folklore-comparative analysis
Keywords: Uzakbergenly Berdimurat Bekbergen Uulu, “Sarysha Aym Tolgavy,” Karakalpak people, Nogai era, traditional culture and oral art, religious beliefs, love, lamentation, patriotism.